FEATURES OF LIFE SATISFACTION IN PEOPLE WITH DIFFERENT ATTITUDE TOWARDS MONEY AND THEIR OWN GREED - Яновська, Світлана Германівна; Криворучко, Світлана Миколаївна; Самохін, Олексій Олексійович; Кононенко, Неллі Миколаївна; Білоус, Наталія Сергіївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
The article deals with the peculiarities of life satisfaction in people with different attitudes towards money and their own greed. It is shown that the majority of subjects are dissatisfid with life, they determine the average level of greed and their money evaluation is conflcting. It was determined that life satisfaction was associated with the self-esteem of greed and attitude towards money. Life satisfaction has a direct connection with the factors «Evaluation», «Power», «Activity» of the concept of money. Hence, a person who highly evaluate money spends it on something that raises his pleasure or saves, which also gives him a sense of satisfaction with life. The money for this person is what affects life, gives strength and opportunity to improve himself and the surrounding world. But the satisfaction of one›s own life can also affect the evaluation of money. A person can understand that money does not always solve life problems, that the growth of money, or their reduction, can go out of control and drastically change the standard of living. It was defied the connection of life satisfaction and such self-esteem factors as greed, feedback factor «Boundless Greed» and a direct connection with the factors «Prudent Greed» and «Smart Greed.» The last two factors of greed self-esteem indicate a person›s prudence and foresight, the harmony of earnings and expenses. And it gives pleasure, because people want something that can afford be doesn’t limits life pursuit of wealth and fortune, she has time to communicate with loved ones and nature classes favorite thing, he lives and enjoys. rite thing, he lives and enjoys.